A novel Fe–La-doped hierarchical porous silica magnetic adsorbent for phosphate removal. Issue 90 (14th September 2016) - Wang, Chun; Zheng, Xudong; Zhang, Fusheng; Huang, Yongqiang; Pan, Jianming
Abstract : A novel Fe–La modified magnetic hierarchical porous silica was synthesized by an impregnation method to adsorb phosphate in aquatic ecology. Abstract : Many rivers and lakes contain excess phosphate, which would cause a series of environmental problems. A novel Fe–La modified magnetic hierarchical porous silica was synthesized by an impregnation method to adsorb phosphate in aquatic ecology. Scanning electron microscopy and transmission electron microscopy suggested the structure of the adsorbent was a core–shell structure. Fourier transform infrared spectroscopy and low-angle powder X-ray diffraction indicated that adsorbents were successfully modified by Fe oxide and La oxide. After loading Fe oxide and La oxide on the material, N2 adsorption–desorption studies showed that the specific surface area was 52.4 m 2 g −1 . Moreover, the adsorbents possessed the desired property of a magnet and easy separation from the solution by testing with a vibrating sample magnetometer. The adsorption process was highly pH-dependent and the appropriate adsorption pH range was about 3.0–6.0. And the resulting adsorption isotherms of the sorbent was better represented by the Langmuir model than the Freundlich model, and the adsorption capacity of the adsorbent was as high as 71.99 mg P per g, which was much higher than most other adsorbents (most La-doped adsorbents' adsorption capacities are under 25 mg P per g). Furthermore, adsorption kinetics studies showed that the adsorption fitted the pseudo-second order model well. Also a high selectivity of phosphate was observed in the coexisting anions system. The proposed adsorbent demonstrated a higher degree of reusability in a cycle test.